Current Aspects of the Planning and Operating Corporate Info-Communication and CRM Systems - Henriette Fábián; Gábor Juhász (Humán Innovációs Szemle, 2023)
The establishment of an up-to-date, modern corporate info-communication system means the development of an integrated system in which information is transmitted practically within a single network. The main advantage of this is less information loss and communication noise, and the system is also more cost-effective. If the information communication technologies used by companies are incomplete or outdated, there is a greater chance that so-called communication noise will occur, i.e. communication, the delivery of messages, and understanding between the communicating parties will become more difficult and complicated. By the end of the nineties, a so-called network society has emerged that was active in virtual space. They have the ability to form smaller groups relatively easily and quickly, among which there is a continuous exchange of information. The members of this network society mostly belong to the so-called Generation Z (those born after the mid-1990s). Among other things, it is typical of this generation that they spend most of their time keeping contact online, therefore their communication, relationship-building and cognitive style also develops accordingly. The technique of the written text, which has been used for centuries, has now been mostly replaced by networked communication, which creates a new kind of collectivity. Due to the linear organization of written and spoken language, it only allows for personal contact with a small group, thus resulting in a certain degree of isolation. The network-like structuring of multimedia seems to be a much more natural form of organization for the human brain, it allows people to keep in touch with a larger number of people. However, these relationships are role-based and less personal: these are the "weak" social ties that we like to rely on when looking for work and making deals. It can therefore be expected that technological changes will result in rapid transformations in our relationship management communication patterns, enabling the creation of a wider network of relationships.